2014
DOI: 10.1021/ol503404p
|View full text |Cite
|
Sign up to set email alerts
|

RhIII-Catalyzed Redox-Neutral C–H Activation of Pyrazolones: An Economical Approach for the Synthesis of N-Substituted Indoles

Abstract: A new strategy is reported for the economical synthesis of indoles bearing an N-(3-aminobut-2-enoyl) substituent through Rh(III)-catalyzed redox-neutral C-H activation of pyrazolones and alkynes. This approach utilizes cheap substrates and mild reaction conditions to access a unique class of indoles via a N-N bond oxidative cleavage without loss of the N-terminus, therefore meeting all the atom/step/redox economy principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 71 publications
0
22
0
1
Order By: Relevance
“…It is found that the two N-N bond cleavage steps via TSII-III and TS5-6 involve significantly different reaction modes: the former being oxidation addition and the latter being natural cleavage in which the σ-bonding electron pair between N1 and N2 goes back to the N2 atom. 30 To better understand the feasible pathway for N-N bond cleavage under given experimental conditions, we explore the electronic behavior of the transformation from 5 to TS5-6. 4 that the N-N bond distance is elongated from 1.98 Å in TS5-6 to 2.15 Å in TSII-III, implying that the transition state TS5-6 appears much earlier than TSII-III.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the two N-N bond cleavage steps via TSII-III and TS5-6 involve significantly different reaction modes: the former being oxidation addition and the latter being natural cleavage in which the σ-bonding electron pair between N1 and N2 goes back to the N2 atom. 30 To better understand the feasible pathway for N-N bond cleavage under given experimental conditions, we explore the electronic behavior of the transformation from 5 to TS5-6. 4 that the N-N bond distance is elongated from 1.98 Å in TS5-6 to 2.15 Å in TSII-III, implying that the transition state TS5-6 appears much earlier than TSII-III.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] In contrast, nevertheless, the C-H activations using a DG ox bearing a N-N bond have been relatively less investigated. 30 As shown in Scheme 1, in the presence of the base NaOAc, the treatment of the representative pyrazolone (R1) with diphenylacetylene (R2) employing [RhCp*Cl 2 ] 2 as the catalyst evolves into the N-(3-aminobut-2-enoyl)-substituted indole P in PhBr solvent at 130°C with a yield of 75%. 30 As shown in Scheme 1, in the presence of the base NaOAc, the treatment of the representative pyrazolone (R1) with diphenylacetylene (R2) employing [RhCp*Cl 2 ] 2 as the catalyst evolves into the N-(3-aminobut-2-enoyl)-substituted indole P in PhBr solvent at 130°C with a yield of 75%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical TLC was performed using 2.5 5cmp lated coated with 0.25 mm thickness of silica gel (60F-254 Merck) and visualization was accomplished with UV light or I 2 /K MnO 4 staining. 1 Ha nd 13 CNMR spectra were obtained from Bruker Ascend 500 MHz spectrophotometer operating at 500.3 MHz for 1 Ha nd 125.8 MHz for 13 Ce xperiments. The chemical shifts are reported in ppm scale with respect to CDCl 3 (7.3 ppm) for 1 Ha nd (77.0 ppm) for 13 CNMR as internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Ar ange of DGs has been employed for the oxidative annulation of anilines. In this context,a cetyl, [7] triazenes, [8] hydrazines, [9] urea, [10] N-heterocy-cles, such as pyridine, [11] pyrimidine, [12] pyrazolone, [13] and purines, [14] have been reported. Despiteo fe ncouraging precedence, most of the N-heterocyclic DG'sa re difficult to install and remove.…”
Section: Introductionmentioning
confidence: 99%